O-178 Occupational radon exposure in Canada. (14th March 2023) - Peters, Cheryl; Brobbey, Anita; Rydz, Ela; Fenton, Shelby; Demers, Paul; Ge, Calvin
Abstract : Introduction: Radon is an established lung carcinogen concentrating in indoor environments with importance for many workers worldwide. However, a systematic assessment of radon levels faced by all workers, not just those with direct uranium or radon exposure, has not previously been completed. The objective of this study was to estimate the prevalence of workers exposed to radon, and the level of exposure (>100–200 Bq/m3, 200–400 Bq/m3, 400–800 Bq/m3, and >800 Bq/m3) in a highly exposed country (Canada). Materials and Methods: Exposures among underground workers were assessed using the CAREX Canada approach. Radon concentrations in indoor workplaces, obtained from two Canadian surveys, were modelled using lognormal distributions. Distributions were then applied to the susceptible indoor worker population to yield the number of exposed workers, by occupation, industry, province, and sex. CAREX Canada received an exemption from ethics approval for this study since all no personal data was used; all data on human subjects was publicly available. Results: In total, an estimated 603, 000 out of Canada's 18, 268, 120 workers are exposed to radon in Canada. An estimated 52% of exposed workers are women, even though they comprise only 48% of the labour force. The majority (68%) are exposed at a level of >100–200 Bq/m3. Workers are primarily exposed in educational services, professional, scientific and technical services, and health care and social assistance, but workers in mining, quarrying, and oil and gas extraction have the largest number of exposed workers at high levels (>800 Bq/m3). Overall, a significant number of workers are exposed to radon, many of whom are not adequately protected by existing guidelines. Conclusions: Radon surveys across multiple industries and occupations are needed to better characterize occupational exposure. These results can be used to identify exposed workers, and to support lung cancer prevention programs within these groups.